Electro-osmotic stabilization of soft Bangkok clay - Chaudhary, Sushil Kumar; Balasubramaniam, A.S.; Bergado, Dennes T.; Guey, Lin Der; Austrian Government (Bangkok : Asian Institute of Technology, 1998)
A comprehensive experimental investigation on the electro-osmotic consolidation of soft Bangkok clay was performed to assess the effectiveness of the treatment and to study the mechanism of the process. Existing oedometer and triaxial cells were modified which allowed the measurement of settlement and pore pressure at anode. Results showed that appreciable chemical changes occur during electro-osmosis which affect the development of negative pore pressure, settlement, and increase in strength of soil. The voltage gradient became non-linear, pH values rose to 12.9 at cathode and decreased to 4.4 at anode. Current density decreased to only a :fraction of its initial value by the end of primary consolidation. In current controlled tests, voltage gradient increased to several times greater than its initial value. Strength increase as much as 126% with reduction in moisture content of 36% was observed with an applied voltage gradient of 55.0 V/m. The negative pore pressure developed at anode was 290.13 kPa. Theoretical predictions grossly underestimated the measured values of negative pressure. Coefficient of electro osmotic permeability increased in the beginning and then converged to a value of 4.5 x 10-5 cm .'s-V at higher voltage gradients. Polarity reversal improved uniformity of the treatment and decreased electrochemical changes, but it did not increase the magnitude of negative pore pressure at anode in 48 hours of treatment. This is believed to be due to ion segregation during the treatment.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Soil consolidation test